Factors Affecting the Menstrual Cycle in Adolescent Girls at SMA Negeri 1 Kluet Selatan, South Aceh Regency, Aceh Province in 2023 - Nasution, Ramadhani Syafitri; Nasution, Zuraidah; Nazilla, Erla Maybi (Universitas Ibn Khaldun Bogor, 2024)
The menstrual cycle is a problem among teenagers. The number of women who experience abnormal menstrual cycle problems caused by many factors, one of which is nutritional status, stress, physical activity and menarche age. Abnormal cycles are generally caused by unstable hormonal levels. Abnormal menstrual cycles cause long-term disruption to the reproductive system if left untreated. This type of research is an analytical survey research with a Cross Sectional research design. The purpose of the study was to find out the factors that affect the menstrual cycle in adolescent girls at SMA N 1 Kluet Selatan. The sample in this study is a student of SMA N 1 Kluet Selatan Class X, XI and XII which was obtained through the probability sampling technique, which is sampling that provides the same opportunity for population members to be selected as sample members. The results of the study showed that there was an effect of nutritional status with a P value of 0.003 (< 0.05), stress with a P value of 0.002 (< 0.05), physical activity with a P value of 0.026 (< 0.05. Menarche age, with a P value of 0.000 (< 0.05) on the menstrual cycle in adolescent girls at SMA N 1 Kluet Selatan From the results of the research, it was found that there was an effect of nutritional status, stress, physical activity, and menarche age on the menstrual cycle in adolescent girls at SMA N1 Kluet Selatan. The suggestion in this study is that it is hoped that adolescent girls can find information about factors that can affect the menstrual cycle so that they can find out early and can overcome the occurrence of disturbances during menstruation.